2022
DOI: 10.1039/d2ob00044j
|View full text |Cite
|
Sign up to set email alerts
|

SN- and NS-puckered sugar conformers are precursors of the (6–4) photoproduct in thymine dinucleotide

Abstract: The S conformation of at least one sugar residue in the TT site is crucial for (6–4) PP formation. This S sugar can be located at the 5′- or 3′-end of the TT site. The 5′-end S conformer location is the most efficient at providing (6–4) PP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…So far, the photochemistry of ten modified dinucleotides ( 2–11 ) has been reported with various degrees of precision. 14,18 Seven of those dinucleotides ( 5–11 , Fig. 3) contain the canonical phosphodiester linkage between modified sugar residues and the other three ( 2–4 , Fig.…”
Section: Design Of Dinucleotidesmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, the photochemistry of ten modified dinucleotides ( 2–11 ) has been reported with various degrees of precision. 14,18 Seven of those dinucleotides ( 5–11 , Fig. 3) contain the canonical phosphodiester linkage between modified sugar residues and the other three ( 2–4 , Fig.…”
Section: Design Of Dinucleotidesmentioning
confidence: 99%
“…Experimentally scrutinizing the relative formation of (6–4)/CPD at the dithymine dinucleotide DNA level, we previously reported that the ground-state conformation of sugar could dramatically drive (6–4) PP formation in a quantitative manner. 14 With this crucial and recently collected information in hand, we think it is now possible and timely to envision a search for candidates able to specifically increase the efficiency of (6–4) PP formation without affecting that of CPD. Such compounds would undoubtedly give access to the ground-state conformation of precursor species prone to oxetane formation.…”
Section: Introductionmentioning
confidence: 99%